Comparison of bacang mango leaf extract concentrations (25%, 50%, and 75%) in inhibiting Streptococcus mutans in vitro - Hutagalung, Mangatas Halomoan Parluhutan; Erawati, Suci; Lumbansiantar, Ruben Tutamana (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2025)
Observations in Pancur Batu District, Deli Serdang Regency, revealed an abundant growth of Bacang mango trees (Mangifera foetida), yet their potential benefits remain underutilized by the local community. This study aimed to investigate and provide insight into the antibacterial properties of Bacang mango leaf extract. An experimental laboratory study was conducted using a randomized posttest-only control group design. The results demonstrated that Bacang mango leaf extract effectively inhibited the growth of Streptococcus mutans in vitro, surpassing the efficacy of 0.2% chlorhexidine digluconate used as a positive control. Measurement of the inhibition zone diameters indicated a proportional relationship between extract concentration and antibacterial efficacy. At 25% concentration, the mean inhibition zone diameter was 13.15 ± 0.49 mm. Increasing the concentration to 50% yielded a larger diameter of 15.75 ± 0.66 mm, while the highest antibacterial activity was observed at 75% concentration, with an inhibition zone diameter of 16.73 ± 0.55 mm. In comparison, the 0.2% chlorhexidine digluconate positive control produced an inhibition zone diameter of only 12.50 ± 0.26 mm. These findings suggest that Bacang mango leaf extract at 75% concentration is the most effective in inhibiting Streptococcus mutans growth. Its significantly greater inhibitory effect relative to lower concentrations and the positive control highlights its potential as a natural antibacterial agent.